Crowd-Sourced Evaluation: A Qualitative Study of User-Generated Product Review Videos on ExpoTV.com - Kurt Wilson (Journal of MultiDisciplinary Evaluation)
Background: While user-generated videos are typically associated with humorous or shocking videos far removed from the rigorous world of evaluation, this paper explores the potential for utilizing user-generated videos as evaluation data.  This topic is addressed through a qualitative pilot study of product review videos available on the ExpoTV.com website.  The findings from this important subset of the evaluation field are analyzed with the goal of identifying themes and insights that could be useful to the broad field of evaluation.